Generación de anticuerpos mediante inoculación de ADN desnudo en un modelo animal - Gómez Treviño, Alberto; Cantú Cárdenaz, Ma. Elena; De la Rosa Moreno, Eduardo l.; Ortiz Martinez, Margarita; Vázquez, Arturo S.; Mercadé Gil, Elena (Universidad Autónoma de Nuevo León, 2010)
Antibody generation was possible by inoculation of DNA plamids encoding the fusogenic F protein of the paramyovirus SVS in rabbit. The presence of antibodies was tested on culture cells expressing the F protein transducted with recombinant adenoviruses.